2005
DOI: 10.1021/om0491701
|View full text |Cite
|
Sign up to set email alerts
|

2-(Aminomethyl)pyridine−Phosphine Ruthenium(II) Complexes:  Novel Highly Active Transfer Hydrogenation Catalysts

Abstract: The complexes trans,cis-RuCl2(PPh3)2(ampy) (1) and trans-RuCl2[Ph2P(CH2)4PPh2](ampy) (2) have been prepared in high yield by reaction of RuCl2(PPh3)3 and RuCl2(PPh3)[Ph2P(CH2)4PPh2] with 2-(aminomethyl)pyridine (ampy) at room temperature by PPh3 displacement. Heating compound 1 in refluxing toluene leads to the isomer cis,cis-RuCl2(PPh3)2(ampy) (3), which has been proven to be a good precursor for the preparation of the complexes cis-RuCl2(PP)(ampy) [PP = (S,S)-Chiraphos, 4; Ph2P(CH2)3PPh2, 5; (S,S)-Skewphos, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
118
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(128 citation statements)
references
References 76 publications
8
118
1
1
Order By: Relevance
“…Precatalysts C1-C3 use the ''NH effect'' described above. [111][112][113] A turnover frequency, defined as moles of product per mol of catalyst per hour, of 30,000 h À1 is achieved by using of C2 and an alkaline base in 2-propanol. 112 A Rh complex C3 is an isolobal to the corresponding arene-Ru complex (see Figure 1.23).…”
Section: Transfer Hydrogenation Of Ketonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Precatalysts C1-C3 use the ''NH effect'' described above. [111][112][113] A turnover frequency, defined as moles of product per mol of catalyst per hour, of 30,000 h À1 is achieved by using of C2 and an alkaline base in 2-propanol. 112 A Rh complex C3 is an isolobal to the corresponding arene-Ru complex (see Figure 1.23).…”
Section: Transfer Hydrogenation Of Ketonesmentioning
confidence: 99%
“…[111][112][113] A turnover frequency, defined as moles of product per mol of catalyst per hour, of 30,000 h À1 is achieved by using of C2 and an alkaline base in 2-propanol. 112 A Rh complex C3 is an isolobal to the corresponding arene-Ru complex (see Figure 1.23). 113 The Ru complexes C4 114 and C5 115 without NH group in ligand catalyze the reaction by different mechanisms.…”
Section: Transfer Hydrogenation Of Ketonesmentioning
confidence: 99%
“…[13] Baratta's catalyst 17 [14] provided up to 71 % conversion to 2 at S/C 1000:1 in iPrOH/tBuOK (entry 4) and 36 % conversion at S/C 2,000:1 (entry 5). Catalyst 18 [15] provided increased activity with full conversion at S/C 2000:1 in MeOH with 5 % tBuOK (60 8C and 27 bar H 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…These have been demonstrated to be powerful catalysts for the enantioselective reduction of ketones and imines. Recently, Baratta and co-authors [11] found that 2-(aminomethyl) pyridine (ampy) accelerated the transfer hydrogenation (TH) of ketones [12][13][14] in Ru(II) and Os(II) complex catalysts. Very recently, Morris group [15,16] reported that chiral NNPP ligands and their iron(II) complexes were effective in the ATH of ketones under mild conditions, representing a rare case of using inexpensive iron as the active metal.…”
Section: Introductionmentioning
confidence: 99%